2010
DOI: 10.1007/s00330-010-1970-9
|View full text |Cite
|
Sign up to set email alerts
|

CT comparison of visual and computerised quantification of coronary stenosis according to plaque composition

Abstract: Objective To compare the diagnostic performance of computerised quantification with visual assessment for the detection of significant coronary stenosis using MDCT, and to determine the impact of plaque composition on diagnostic procedure. Methods We retrospectively evaluated 1564 coronary segments of 127 patients who underwent 64-slice MDCT and quantitative coronary angiography (QCA). The lesions were analysed with both methods of visual assessment and computerised quantification using an automatic vessel con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The greater volumes of lower density plaque in populations with greater likelihood of CAD would, therefore, not only result in poor reproducibility of non-calcified plaque but also of geometrical, distributional, burden and volume related parameters. This is exemplified by the findings of Kang et al who reported a decreased sensitivity to detect diameter stenosis >50% in non-calcified plaque due to underestimation when using automated techniques compared with visual assessments[25]. Furthermore, increased disease burden potentially requires greater manual correction when using semi-automated quantification techniques, thereby introducing greater variability into QCT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The greater volumes of lower density plaque in populations with greater likelihood of CAD would, therefore, not only result in poor reproducibility of non-calcified plaque but also of geometrical, distributional, burden and volume related parameters. This is exemplified by the findings of Kang et al who reported a decreased sensitivity to detect diameter stenosis >50% in non-calcified plaque due to underestimation when using automated techniques compared with visual assessments[25]. Furthermore, increased disease burden potentially requires greater manual correction when using semi-automated quantification techniques, thereby introducing greater variability into QCT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies examined the accuracy of SVE using a small number of readers reviewing a large number of images (11)(12)(13); however, these studies did not involve readers across several subspecialties, which limits their findings from being widely applicable. Also, the accuracy of estimation in relation to physician experience is unknown.…”
mentioning
confidence: 98%
“…An automatic vessel detection tool on curved multi-planar reconstructions and cross-sectional images perpendicular to the vessel was used to initially segment the coronary artery, as described previously (9). Two cardiologists blinded to the clinical and ICA data (GL and WT, with at least 5 years of experience in cardiovascular CT imaging and ICA) first evaluated the cCTA images to determine if the segments containing calcium were interpretable and graded the stenosis severity at the site of calcification.…”
Section: Methodsmentioning
confidence: 99%
“…Non-diagnostic CAC was defined as a totally calcified plaque or predominantly calcified plaque (plaque with less than 50% non-calcified component), in which significant luminal narrowing (>50%) could not be entirely excluded by the cCTA reader solely due to a potential blooming artifact (no signs of motion, streak, or windmill artifacts, incomplete coverage, or increase background noise levels). An automatic vessel detection tool on curved multiplanar reconstructions and cross-sectional images perpendicular to the vessel was used to initially segment the coronary artery, as described previously (9). Two cardiologists blinded to the clinical and ICA data (GL and WT, with at least 5 years of experience in cardiovascular CT imaging and ICA) first evaluated the cCTA images to determine if the segments containing calcium were interpretable and graded the stenosis severity at the site of calcification.…”
Section: Ccta Image Analysis (Part B)mentioning
confidence: 99%